2019
DOI: 10.5194/wes-2019-65
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Analytical model for the power-yaw sensitivity of wind turbines operating in full wake

Abstract: Abstract. Wind turbines are designed to align themselves with the incoming wind direction. However, turbines often experience unintentional yaw misalignment, which can significantly reduce the power production. The unintentional yaw misalignment increase for turbines operating in wake of upstream turbines. Here, the combined effects of wakes and yaw misalignment are investigated with the resulting reduction in power production. A model is developed, which considers the trajectory of each turbine blade element … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…The uncertainties and sensitivities in this study associated with the wall model, subfilter scale model, wind turbine model, and ABL characteristics such as boundary layer inversion height were not investigated in detail and are left for future work. More reliable and generalizable estimates for P p (Liew et al, 2019), or generally C p as a function of γ, should be investigated. Future work should also investigate the influence of latitude and geostrophic wind direction on wake steering control performance (Howland et al, 2020a).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The uncertainties and sensitivities in this study associated with the wall model, subfilter scale model, wind turbine model, and ABL characteristics such as boundary layer inversion height were not investigated in detail and are left for future work. More reliable and generalizable estimates for P p (Liew et al, 2019), or generally C p as a function of γ, should be investigated. Future work should also investigate the influence of latitude and geostrophic wind direction on wake steering control performance (Howland et al, 2020a).…”
Section: Discussionmentioning
confidence: 99%
“…However, simulations have shown for the NREL 5 MW turbine that P p = 1.88 (Gebraad et al, 2016a). Recent work has shown that P p differs for freestream and waked turbines (Liew et al, 2019). The value of P p that results in a satisfactory agreement with experimental data depends on the wind turbine model, ABL shear and veer, and atmospheric stability.…”
Section: Lifting Line Wake Modelmentioning
confidence: 97%
“…5. The reduction in the cumulative power output is even more pronounced at large yaw angles of the downstream turbine, ψ 2 , as the power decrease for a yawed turbine operating in wake is increased compared to a freestanding turbine; see Liew et al (2019). Furthermore, the effect of wake deflection is clearly visible in Fig.…”
Section: Wake Deflection and Velocity Deficitmentioning
confidence: 91%
“…The potential for wake steering to increase wind farm power production depends on the magnitude of wake interactions between the wind turbines, the magnitude of the wake deflection as a function of yaw misalignment, and the power production lost by the yaw misaligned turbines 10 . The power production of a wind turbine in yaw misalignment is often modeled 3,11 as…”
Section: Introductionmentioning
confidence: 99%